Gold dinar acceptance in modern monetary system: Empirical evidence in the context of gold dinar community in Malaysia / Ruzanifah Kosnin - Kosnin, Ruzanifah (Institute of Graduate Studies, UiTM, 2018)
The unstable and unjust fiat money system gave rise to the need to relook the role of gold as real money with stable values. Despite the advantage of gold (or gold dinar) as a stable and just medium in a monetary system, its implementation in the current system is challenging. Regardless of the challenges, effort in bringing a just monetary system has echoed in some countries and one of the most important elements to ensure the success of the implementation is the level of acceptance among the people. Therefore, the focus of this research is to investigate the comprehensive factors of gold dinar acceptance in order to understand gold dinar phenomenon in modern monetary system. The three main objectives of this research are as follows: (1) to identify factors contributing to the acceptance of gold dinar, (2) to provide an understanding of Islamic values in the practice of gold dinar and its role as money, and (3) to test and validate the Gold Dinar Acceptance Model (GDAM). A researchbased model incorporating several theories of behavioural acceptance as well as emerging new factors known as perceived Islamic values and perceived knowledge was adopted to explain the relationships among various variables and to better understand the motivational factors underlying gold dinar acceptance. Exploratory studies using semi-structured interviews, observations and document analysis were employed to achieve the first two research objectives. Then 403 data collected using cross-sectional survey questionnaire from online gold dinar community in Malaysia to answer the third research question…